Diuretic vs. placebo in intermediate-risk acute pulmonary embolism: a randomized clinical trial. Issue 1 (11th October 2021) - Lim, Pascal; Delmas, Clément; Sanchez, Olivier; Meneveau, Nicolas; Rosario, Roger; Bouvaist, Helene; Bernard, Anne; Mansourati, Jacques; Couturaud, Francis; Sebbane, Mustapha; Coste, Pierre; Rohel, Gwenole; et al.
Abstract: Aims: The role of diuretics in patients with intermediate-risk pulmonary embolism (PE) is controversial. In this multicentre, double-blind trial, we randomly assigned normotensive patients with intermediate-risk PE to receive either a single 80 mg bolus of furosemide or a placebo. Methods and results: Eligible patients had at least a simplified PE Severity Index (sPESI) ≥1 with right ventricular dysfunction. The primary efficacy endpoint assessed 24 h after randomization included (i) absence of oligo-anuria and (ii) normalization of all sPESI items. Safety outcomes were worsening renal function and major adverse outcomes at 48 hours defined by death, cardiac arrest, mechanical ventilation, or need of catecholamine. A total of 276 patients underwent randomization; 135 were assigned to receive the diuretic, and 141 to receive the placebo. The primary outcome occurred in 68/132 patients (51.5%) in the diuretic and in 49/132 (37.1%) in the placebo group (relative risk = 1.30, 95% confidence interval 1.04–1.61; P = 0.021). Major adverse outcome at 48 h occurred in 1 (0.8%) patients in the diuretic group and 4 patients (2.9%) in the placebo group ( P = 0.19). Increase in serum creatinine level was greater in diuretic than placebo group [+4 µM/L (−2; 14) vs. −1 µM/L (−11; 6), P < 0.001]. Conclusion: In normotensive patients with intermediate-risk PE, a single bolus of furosemide improved the primary efficacy outcome at 24 h and maintained stable renal function. In the furosemide group, urine output increased, without a demonstrable improvement in heart rate, systolic blood pressure, or arterial oxygenation. ClinicalTrials.gov identifier NCT02268903. Graphical abstract: